Effects of microalgae-bacteria inoculation ratio on biogas slurry treatment and microorganism interactions in the symbiosis system - Huang, Qiaoyun; Yan, Hongbin; Liu, Yuhuan; Cui, Xian; Wang, Yunpu; Yu, Zhigang; Ruan, Roger; Zhang, Qi (Journal of cleaner production, 2022)
The improper disposal of biogas slurry will result in significant pollution of the environment. Microalgae-bacteria symbiosis systems can effectively treat biogas slurry while also producing useful biomass. In this study, Chlorella vulgaris (C.V) and indigenous Shinella sp. YHB03 (S.S) were co-cultured and mono-cultured to purify biogas slurry. The inoculation ratio of C.V and S.S in the co-culture was optimized. The enhancement rate was creatively introduced to quantitatively analyze the changes between co-cultures and mono-cultures. The introduction of S.S into the C.V culture increased the carbon emission reduction capacity of the system, improved the microbe's tolerance to biogas slurry, and raised algal cell viability. Biomass production, pollutants removal and value-added products output were significantly enhanced when co-cultured C.V with S.S. And as the inoculation ratio of C.V and S.S increased from 2:1 to 50:1, this synergistic effect increased at first, then dropped, with 20:1 being the optimal. When co-cultured C.V with S.S at inoculation ratio of 20:1, the microalgae cell viability attained 84.84%, the biomass productivity reached 80 mg·L−1·day−1, and the NH4+-N, TP, TOC and IC removal efficiencies achieved 72.2%, 48.3%, 65% and 63.4%, respectively. This study provides an environmentally sustainable strategy for biogas slurry treatment. [Display omitted] •Co-culture enhanced the removal of pollutants and the output of biomass.•Bacteria reduced the oxidative stress of pollutant to microalgae.•Bacteria improved the cell activity of microalgae.•Symbiosis of microalgae and bacteria reduced carbon emission.•The optimum inoculation ratio of microalgae and bacteria is 20:1.